Back Cover: Supported Anionic Gold Nanoparticle Catalysts Modified Using Highly Negatively Charged Multivacant Polyoxometalates (Angew. Chem. Int. Ed. 34/2022). Issue 34 (27th July 2022) - Xia, Kang; Yatabe, Takafumi; Yonesato, Kentaro; Yabe, Tomohiro; Kikkawa, Soichi; Yamazoe, Seiji; Nakata, Ayako; Yamaguchi, Kazuya; Suzuki, Kosuke
Abstract : Supported gold nanoparticle catalysts have attracted growing interest in aerobic oxidation reactions. In their Research Article (e202205873 ), Kazuya Yamaguchi, Kosuke Suzuki et al. describe a method for the design of supported anionic gold nanoparticle catalysts using negatively charged multivacant polyoxometalates. The electronic states of the catalysts can be sequentially modulated, and the catalyst prepared using [SiW9 O34 ] 10− acted as a reusable heterogeneous catalyst, showing superior catalytic activity and enhanced stability compared to conventional catalysts.